2022
DOI: 10.1007/s40122-022-00361-5
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Dexmedetomidine or Lidocaine Infusion for the Prevention of Chronic Postoperative and Neuropathic Pain After Gynecological Surgery: A Randomized, Placebo-Controlled, Double-Blind Study

Abstract: Introduction:The transition of acute to chronic postoperative pain (CPP) remains a significant burden to the rehabilitation of patients. The research for adjuvants to prevent CPP continues; among others, dexmedetomidine and lidocaine seem promising agents. Methods: This is a long-term follow-up of a randomized, placebo-controlled, double-blind study on women who underwent open abdominal gynecological surgery and received dexmedetomidine or lidocaine or placebo infusion perioperatively (n = 81). The effect of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 46 publications
2
11
1
Order By: Relevance
“…However, the difference was small and may be of limited clinical importance. Ours differs from a study by Rekatsina et al, 31 which showed that dexmedetomidine significantly reduced pain scores, but did not reduce the incidence of neuropathic pain (Douleur Neuropathique 4 score >4). This inconsistency may be due to the different diagnostic scales of neuropathic pain used and the sample size.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, the difference was small and may be of limited clinical importance. Ours differs from a study by Rekatsina et al, 31 which showed that dexmedetomidine significantly reduced pain scores, but did not reduce the incidence of neuropathic pain (Douleur Neuropathique 4 score >4). This inconsistency may be due to the different diagnostic scales of neuropathic pain used and the sample size.…”
Section: Discussioncontrasting
confidence: 99%
“…4,5 Previous studies have shown that dexmedetomidine provides effective postoperative early analgesia and reduced postoperative opioid requirements for different types of surgeries. [6][7][8][9] Furthermore, a meta-analysis indicated that dexmedetomidine relieved postoperative acute pain intensity and reduced perioperative analgesic consumption in neurosurgery, but the impact of dexmedetomidine on chronic pain needs further study. 10 It has been reported that postoperative acute pain correlates with an increased risk of chronic pain.…”
Section: Anesthesia and Analgesiamentioning
confidence: 99%
“…Dexmedetomidine is commonly used as an adjuvant analgesic in clinical practice and has a good synergistic effect with opioids without causing respiratory depression . The unremarkable improvement in pain on movement can be attributed to the dose we administered (0.04 μg/kg/h), which is much lower compared with the standard clinical dose (0.6 μg/kg/h) …”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine, a highly selective α2 adrenoreceptor agonist, reduces postoperative pain and opioid use in the acute phase [ 29 ]. In a prospective study, it was also associated with significantly less CPSP [ 30 ]. In our study, the use of dexmedetomidine peri- and postoperatively was significantly lower in the CPSP group but is not significant in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%